Tokyo Court Decisions Regarding a Request for the Return of a Child to Turkey and a Brief Reference to the Japanese Practice - Onur Can Saatcıoğlu (Public and Private International Law Bulletin)
Japan refrained from becoming a party to the Convention of 25 October 1980 on Civil Aspects of International Child Abduction for nearly thirty years following its completion. Due to this choice, Japan received enormous pressure from numerous states, all of which eventually led to Japan becoming a member state, and thus, starting from 1 April 2014, applying the Convention. The Japanese implementation act was drafted completely mindful of the particular needs and priorities of Japan and therefore ended up being a customized text. In the Act, the provision related to the “grave risk” exception of art.13(1)b of the Convention was stipulated in a broader scope than the original rule, with an aim to guide Japanese courts dealing with matters which may fall under this exception. The first time this provision was ever applied, the application was made from Turkey and by a Turkish father. The return order given by Tokyo Family Court was challanged by the Japanese mother and ultimately cancelled by Tokyo District Court. This paper aims to translate the above decisions into Turkish and present them in a systematic way. For doing that, however, reasons for Japan’s lateratification and for it’s need of a detailed implementation act must be revealed. Then, following after a short introduction to the general application framework embraced by the Act, the approach regarding the grave risk exception and in which ways it differs from the Convention will be examined. Lastly, the abovementioned two decisions alongside our comments on them will be given.